Folding and unfolding movements in a [2]pseudorotaxane - Suresh, Moorthy; Mandal, Amal Kumar; Kesharwani, Manoj K.; Adarsh, N. N.; Ganguly, Bishwajit; Kanaparthi, Ravi Kumar; Samanta, Anunay; Das, Amitava (Journal of Organic Chemistry, 2011)
A new dibenzo[24]crown-8 derivative (1) was synthesized and functionalized with aromatic moieties such as naphthalene and coumarin units. These two fluorophores are known to form an effective FRET (Forster resonance energy transfer) pair, and this formed the basis for the design of this host crown ether derivative. Results of the steady-state and time-resolved fluorescence studies confirmed the resonance energy transfer between the donor naphthalene moiety and acceptor coumarin fragment, while NMR spectra and computational studies support a folded conformation for the uncomplexed crown ether 1. This was found to form an inclusion complex, a [2]pseudorotaxane type with imidazolium ion derivatives as the guest molecules with varying alkyl chain lengths ([C4mim]+ or [C10mim]+). The host crown ether (1) tends to adopt an open conformation on formation of the interwoven inclusion complex (1·[C4mim]+ or 1·[C10mim]+). This change in conformation, from the folded to a open one, was predicted by computational as well as 1H NMR studies and was confirmed by single crystal X-ray structure for one (1·[C4mim]+) of the two inclusion complexes. The increase in the effective distance between the naphthalene and coumarin moieties in the open conformation of these inclusion complexes was also supported by the decrease in the effective FRET process that was operational between naphthalene and coumarin moieties in the free molecule (1). Importantly, this inclusion complex formation was found to be reversible, and in the presence of a stronger base/polar solvent, such as triethyl amine/DMSO, the deprotonation/effective solvation of the cationic imidizolium ions ([C4mim]+ or [C10mim]+) resulted in decomplexation or dethreading with restoration of the original emission spectra for 1, which signifies the subsequent increase in the FRET process. Thus we could demonstrate that a molecular folding-unfolding type of movement in the crown ether derivative could be induced by chemical input as an imidazolium ion.